If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6b + 62 = 8b + 6 Reorder the terms: 62 + -6b = 8b + 6 Reorder the terms: 62 + -6b = 6 + 8b Solving 62 + -6b = 6 + 8b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-8b' to each side of the equation. 62 + -6b + -8b = 6 + 8b + -8b Combine like terms: -6b + -8b = -14b 62 + -14b = 6 + 8b + -8b Combine like terms: 8b + -8b = 0 62 + -14b = 6 + 0 62 + -14b = 6 Add '-62' to each side of the equation. 62 + -62 + -14b = 6 + -62 Combine like terms: 62 + -62 = 0 0 + -14b = 6 + -62 -14b = 6 + -62 Combine like terms: 6 + -62 = -56 -14b = -56 Divide each side by '-14'. b = 4 Simplifying b = 4
| 3x-3y+7=0 | | 17x-28x-12=21 | | Y+13.4=8.63 | | 2r+10=14 | | 3/5a=18 | | 18b-6= | | -1x+9=7x-5 | | x^6-4x^5+13x^4=0 | | z^4+4iz+10i=0 | | -16y+18=-30 | | (1/5)^(x-9)=5^(7x-5) | | -3+8x=-59 | | 75=25t+4.9t^2 | | 0.6(x-4)=12.0 | | 38a+21-20a=39 | | -1x-9=7x+5 | | 75=25*t+0.5*9.8*t^2 | | 9(x+4)+x=3(x+5)-8 | | -5(y-3y)+9=3(2y-y)+1+12y | | .50c+.40-400=190 | | 0.05x-2.75=0.3(x-5) | | 3=-3(x+4) | | -1x+9=7x+5 | | 6x+2-15=-15 | | .50c+.40=400 | | -3(x+4)+4=7(x+4)+3 | | 5(x-7)+10=3(x-5) | | h(t)=2t-t^2 | | 5sinx+7cosx=8 | | 12x-8=9x-8 | | x-4=-24-9x | | .50c+400=.40 |